In Vitro Recapitulation of Developmental Transitions in Human Neural Stem Cells. (24th August 2019) - Ostermann, Laura; Ladewig, Julia; Müller, Franz-Josef; Kesavan, Jaideep; Tailor, Jignesh; Smith, Austin; Brüstle, Oliver; Koch, Philipp
Abstract : During nervous system development, early neuroepithelial stem (NES) cells with a highly polarized morphology and responsiveness to regionalizing morphogens give rise to radial glia (RG) cells, which generate region-specific neurons. Recently, stable neural cell populations reminiscent of NES cells have been obtained from pluripotent stem cells and the fetal human hindbrain. Here, we explore whether these cell populations, similar to their in vivo counterparts, can give rise to neural stem (NS) cells with RG-like properties and whether region-specific NS cells can be generated from NES cells with different regional identities. In vivo RG cells are thought to form from NES cells with the onset of neurogenesis. Therefore, we cultured NES cells temporarily in differentiating conditions. Upon reinitiation of growth factor treatment, cells were found to enter a developmental stage reflecting major characteristics of RG-like NS cells. These NES cell-derived NS cells exhibited a very similar morphology and marker expression as primary NS cells generated from human fetal tissue, indicating that conversion of NES cells into NS cells recapitulates the developmental progression of early NES cells into RG cells observed in vivo. Importantly, NS cells generated from NES cells with different regional identities exhibited stable region-specific transcription factor expression and generated neurons appropriate for their positional identity. Stem Cells   2019;37:1429–1440 : Abstract : In vivo, neuroepithelial stem cells of the neural tube give rise to radial glia cells of the fetal brain. Stably expandable neuroepithelial stem (NES) cells can be derived from pluripotent stem cells and directly from early-stage human fetal brain tissue. Later-stage human fetal brain tissue gives rise to radial glia-like neural stem (NS) cells. Results of this study showed that radial glia-like NS cells can be directly generated from in vitro expanded NES cells.